POLA PERTUMBUHAN SISWA DI SD LABORATORIUM UNDIKSHA SINGARAJA DAN SDN 3 PANJI, KABUPATEN BULELENG, BALI - Ni Nyoman Dian Anjani; Ni Made Rai Suarni; Dwi Ariani Yulihastuti (Program Studi Biologi Universitas Udayana, 2025)
Growth is a change that occurs quantitatively that can be observed in human physique, such as height, and body weight. The purpose of this research was to determine the growth patterns of student at Elementary School (SD) LAB Undiksha Singaraja and SDN 3 Panji. The research method used purposive sampling, carried out at SD LAB Undiksha Singaraja and SDN 3 Panji with 60 probands aged 10-12 years in January 2023. Observations were made on student height, student weight, student Body Mass Index (BMI), student age at SD LAB Undiksha Singaraja and SDN 3 Panji. Data analysis used the T Test. The results of statistical analysis show that there are insignificant differences in the growth patterns of students at SDN 3 Panji and SD LAB Undiksha Singaraja. The research results showed that the average height and weight of students at SDN 3 Panji was lower than at SD LAB Undiksha Singaraja. The majority of students' BMI at SDN 3 Panji is in the underweight category, namely 60% for boys and 66.67% for girls. The majority of students' BMI at SD LAB Undiksha Singaraja is in the normal category, namely 46.67% for boys and 53.33% for girls. Keywords: Body Mass Index, Panji, growth, Undiksha